2005
DOI: 10.1126/science.1103773
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of the Basidiomycetous Yeast and Human Pathogen Cryptococcus neoformans

Abstract: Cryptococcus neoformans is a basidiomycetous yeast ubiquitous in the environment, a model for fungal pathogenesis, and an opportunistic human pathogen of global importance. We have sequenced its ∼20-megabase genome, which contains ∼6500 intron-rich gene structures and encodes a transcriptome abundant in alternatively spliced and antisense messages. The genome is rich in transposons, many of which cluster at candidate centromeric regions. The presence of these transposons may drive karyotype ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
528
0
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 661 publications
(544 citation statements)
references
References 12 publications
6
528
0
6
Order By: Relevance
“…This suggests that an independent gene duplication event occurred in C. neoformans. Since the genome of C. neoformans was not duplicated during evolution (Loftus et al 2005), chromosomal translocation and segmental duplication processes might have resulted in the duplication of the -CAs. Only recently has the crystal structure of C. neoformans Can2 revealed that the enzyme belongs to the plant-type -CAs (Schlicker et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that an independent gene duplication event occurred in C. neoformans. Since the genome of C. neoformans was not duplicated during evolution (Loftus et al 2005), chromosomal translocation and segmental duplication processes might have resulted in the duplication of the -CAs. Only recently has the crystal structure of C. neoformans Can2 revealed that the enzyme belongs to the plant-type -CAs (Schlicker et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Schizophyllum commune has been reported as the causative agent of maxillary sinus infection (Kern and Uecker, 1986) and Cryptococcus neoformans is a well-studied fungal pathogen (Loftus et al, 2005) that causes life-threatening meningitis in immunocompromised patients (Mitchell and Perfect, 1995). Schizophyllum and Cryptococcus were concentrated in different particle-size ranges, d a o4.7 mm and d a 44.7 mm, respectively, and Schizophyllum was most abundant in the spring (Figure 2).…”
Section: Abundance Of Allergenic and Pathogenic Fungimentioning
confidence: 99%
“…The most striking pattern is that of C. neoformans, which shows a very strong deletion bias (62% of all polymorphisms are deletions). If deletion/insertion bias predicts the direction of genome size evolution (Mira et al 2001), then C. neoformans may be in the process of a genome size reduction, although current gene density is not especially high (Loftus et al 2005).…”
Section: Mutational Spectrum Of the Rdna Polymorphismsmentioning
confidence: 99%
“…However, C. neoformans grows as a yeast and is a severe pathogen of immunocompromised humans. The haploid genome sequence was recently completed by the Stanford Genome Technology Center (Loftus et al 2005) (http://wwwsequence.stanford.edu/group/C.neoformans/index.html).…”
mentioning
confidence: 99%